Peran Kelompok Sadar Wisata (POKDARWIS) dalam Pengembangan Desa Wisata Kampung Melayu Sungai Mempura Kabupaten Siak - Nadatul Mafella; Ikhwani Ratna; Ari Nurwaidah; Hidayati Nasrah (Yayasan Almanar Pujud, 2024)
Research was carried out in Sungai Mempura Village, Siak Regency. The aim of research is to determine the role of the Tourism Awareness Group (Pokdarwis) in developing tourist villages in Sungai Mempura Village, Siak Regency. The type of research used is descriptive qualitative. The data collection techniques used included observation, interviews and documentation with informants, the Head of Sungai Mempura Village, the Tourism Awareness Group, the community of Sungai Mempura Village and tourists. Based on the results of research, the following results were obtained: The Kampung Melayu Sungai Mempura tourist village has a number of an attractive attraction for people with diverse potential. The natural beauty is still preserved, good natural potential and a very beautiful environment and is the center of the Greater Malay Kingdom, commitment to preserving culture is the main magnet. By referring to several indicators used in this research, namely Attraction, Accessibilities, Amenities and Ancillary Services in the development of the Kampung Melayu Sungai Mempura Tourism Village, it looks quite optimal. Inhibiting factors include suboptimal facilities and infrastructure, self-help fund allocation and limited human resources.